2018
DOI: 10.1093/nar/gky1103
|View full text |Cite
|
Sign up to set email alerts
|

3D organization of chicken genome demonstrates evolutionary conservation of topologically associated domains and highlights unique architecture of erythrocytes’ chromatin

Abstract: How chromosomes are folded, spatially organized and regulated in three dimensions inside the cell nucleus are among the longest standing questions in cell biology. Genome-wide chromosome conformation capture (Hi-C) technique allowed identifying and characterizing spatial chromatin compartments in several mammalian species. Here, we present the first genome-wide analysis of chromatin interactions in chicken embryonic fibroblasts (CEF) and adult erythrocytes. We showed that genome of CEF is partitioned into topo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
101
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(132 citation statements)
references
References 88 publications
(132 reference statements)
24
101
1
1
Order By: Relevance
“…melanogaster TADs are highly conserved across cell types, tissues and species (Dixon et al 2012;Vietri Rudan et al 2015;Fishman et al 2019) . To investigate conservation of this spatial structure during Drosophila evolution, we compared TADs between D. pseudoobscura and D. melanogaster , which diverged about ~49 million years ago (Thomas and Hahn 2017) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…melanogaster TADs are highly conserved across cell types, tissues and species (Dixon et al 2012;Vietri Rudan et al 2015;Fishman et al 2019) . To investigate conservation of this spatial structure during Drosophila evolution, we compared TADs between D. pseudoobscura and D. melanogaster , which diverged about ~49 million years ago (Thomas and Hahn 2017) .…”
Section: Resultsmentioning
confidence: 99%
“…Conservation of TAD structures between the two distantly related Drosophila species further prompted us to ask if disruption of TAD integrity (i.e. TAD shuffling or fusing as a result of large-scale chromosomal arrangements) in Drosophila is also constrained during evolution as previously shown in other animals such as mammals (Krefting et al 2018;Lazar et al 2018) and birds (Fishman et al 2019) . We test this by analyzing the distribution of chromosomal rearrangement breakpoints (using synteny breaks as the proxy) along the TAD body.…”
Section: Breaks In Synteny Enriched At Tad Boundariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative studies performed on multiple vertebrate species revealed that genome architecture is evolutionarily conserved and could be explained by dynamic interplay between processes of cohesin-mediated loop extrusion and chromatin compartmentalization [5][6][7][8] . In insects, comprehensive analyses [9][10][11][12][13] and cross-species comparisons 12,14 of genome architecture have to date focused only on Drosophila species.…”
Section: Introductionmentioning
confidence: 99%
“…В нашей лаборатории получены данные о том, что при полной остановке транскрипции в эритроцитах курицы ядро действительно переходит в равновесное состояние: данные, полученные при помощи HiC и электронной микроскопии, говорят о максимально выраженной сегрегации компартментов активного и неактивного хроматина. При этом полученные карты хроматиновых взаимодействий свидетельствуют о полном отсутствии ТАДов и петель (Fishman et al, 2019). Исчезновение регуляторных петлевых взаимодействий не может быть объяснено остановкой транскрипционной активности и, соответственно, продвижения комплекса ассоциированных с транскрипцией белков, поскольку в ядрах сперматозоидов, также транскрипционно неактивных, доменная организация сохранялась.…”
Section: реорганизация архитектуры хроматина в ходе эритропоэзаunclassified